Water infiltration impact on tensile strength and breaking strain of architectural fabrics. Issue 16 (December 2018) - Asadi, Hastia; Uhlemann, Jörg; Stranghöner, Natalie
Architectural fabrics consist of woven base cloth protected by a coating on both sides. Corrosive liquids or vapours may diffuse through the matrix material and corrosion effects on fibres may lead to substantial reduction in mechanical properties. Tensile strength is of most importance for the safety of a structure and strain properties govern its serviceability. Wetting is one of the main environmental impacts. Due to rain, condensation or snow melting cycles, the membrane gets wet. If the fabric under the coating gets wet and to which amount depends on the condition of the covering coating over the lifetime of the architectural structure and on the wicking properties of the fabric material. Water penetration influences the fabric's properties. How and to what extent is the field of investigations of this article. The influence of water on the tensile strength and the breaking strain of two common architectural fabrics, polyester (PES)/ polyvinylchloride (PVC) and glass/polytetrafluoroethylene (PTFE), are investigated. Virgin and aged materials are examined.